PEMBELAJARAN MENAFSIR PANDANGAN PENGARANG DALAM TEKS NOVEL DENGAN MODEL PROBLEM BASED LEARNING BERORIENTASI PADA PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS XII SMA NEGERI 1 CICALENGKA TAHUN PELAJARAN 2023/2024 - Amliah Khirun Nisa; Titin Nurhayatin; Musaddad Abdul Azis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by a problem that often occurs in Indonesian language learning, namely the low critical thinking skills of students, which has an impact on learning outcomes. Having critical thinking skills is one of the learning skills that must be developed in the 21st century which must be achieved by students. Therefore, it is very important to encourage and develop students' critical thinking abilities during the learning process. One way is through learning using the Problem Based Learning model in learning to interpret the author's view of the novel text. The purpose of this research is to test the author's abilities, to test the abilities of class . The method used in the research is quantitative. The data sources in this research are students in class XII IPA 3 (discussion control model) and XII IPA 5 (problem based learning experimental model) at SMA Negeri 1 Cicalengka. Data collection was carried out by means of direct research with a series of learning activities (introductory, core and closing activities). The results of the research found that the critical thinking abilities of students in the experimental class obtained a score of 93.8 with an average value of 2.7. Meanwhile, the control class got a score of 90.7 with an average score of 2.6, meaning that the ability to think critically in learning to interpret the author's view of the novel text in class XII students at SMA Negeri 1 Cicalengka for the 2023/2024 academic year was proven to be effective.